2010
DOI: 10.1021/jp103734c
|View full text |Cite
|
Sign up to set email alerts
|

Reducing of Nitrous Oxide Emissions Using Ionic Liquids

Abstract: This work is focused on the possible capture of nitrous oxide and more precisely protoxide using ionic liquids (ILs). ILs are gaining special attention since the efficiency of many processes can be enhanced by the judicious manipulation of their properties. The absorption of greenhouse gases can be enhanced by the basic character of the IL. In this work, these characteristics are evaluated through the study of the gas-liquid equilibrium of five imidazolium-based ILs: 1-butyl-3-methylimidazolium tetrafluorobora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…The tethering of methoxy groups at the imidazolium ring in [(MeO) 2 Im][PF 6 ] is expected to have a strong influence on the electronic structure of the imidazolium ring compared to 1,3‐dialkylimidazolium systems,38 which can be accessed by XPS as has been previously shown for a thiouronium‐functionalized IL 39. Dialkoxyimidazolium compounds are interesting due to their ability to dissolve a reasonable amount of the greenhouse gases CO 2 40 and N 2 O 41. They are also suitable in synthesis due to the fact that N‐heterocyclic carbenes (NHCs) are easily made from imidazolium‐based ILs which then can serve as catalyst or solvent in reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tethering of methoxy groups at the imidazolium ring in [(MeO) 2 Im][PF 6 ] is expected to have a strong influence on the electronic structure of the imidazolium ring compared to 1,3‐dialkylimidazolium systems,38 which can be accessed by XPS as has been previously shown for a thiouronium‐functionalized IL 39. Dialkoxyimidazolium compounds are interesting due to their ability to dissolve a reasonable amount of the greenhouse gases CO 2 40 and N 2 O 41. They are also suitable in synthesis due to the fact that N‐heterocyclic carbenes (NHCs) are easily made from imidazolium‐based ILs which then can serve as catalyst or solvent in reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[39] Dialkoxyimidazolium compounds are interesting due to their ability to dissolve a reasonable amount of the greenhouse gases CO 2 [40] and N 2 O. [41] They are also suitable in synthesis due to the fact that N-heterocyclic carbenes (NHCs) are easily made from imidazolium-based ILs which then can serve as catalyst or solvent in reactions. It was shown that similar compounds as the [(MeO) 2 Im][PF 6 ], e. g. with a bromo-substituent attached to the C 2 -position or with more bulky substituents, form several metal-NHC-complexes.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 This kind of process has been developed on the basis of the appealing properties of various ILs, such as the mostly studied imidazolium-based ILs. The achievements made by researchers have proved that ILs are promising materials in the application of hazardous gas absorption.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Most importantly, ILs can be functionalized to be task‐specific ILs (TSILs), which enables highly efficient and selective separation or reaction process according to our requirements. As a consequence, ILs have been regarded as a new type of “green solvents” that exhibit extensive potential of application in many fields such as catalysis, electrolysis, extraction, membrane separation, and gas absorption.…”
Section: Introductionmentioning
confidence: 99%